Therapeutic Potential and Molecular Mechanisms of Emblica officinalis Gaertn in Countering Nephrotoxicity in Rats Induced by the Chemotherapeutic Agent Cisplatin - Malik, Salma; Suchal, Kapil; Bhatia, Jagriti; Khan, Sana I.; Vasisth, Swati; Tomar, Ameesha; Goyal, Sameer; Kumar, Rajeev; Arya, Dharamvir S.; Ojha, Shreesh K. (Frontiers in Pharmacology, 2016)
Emblica officinalis Gaertn. belonging to family Euphorbiaceae is commonly known as Indian gooseberry or "Amla" in India. It is used as a ‘rejuvenating herb’ in traditional system of Indian medicine. It has been shown to possess antioxidant, anti-inflammatory and anti-apoptotic effects. Thus, on the basis of its biological effects, the present study was undertaken to evaluate the protective effect of the dried fruit extract of the E. Officinalis (EO) in cisplatin-induced nephrotoxicity in rats and also to evaluate the mechanism of its nephroprotection. The study was done on male albino Wistar rats. They were divided into 6 groups (n=6) viz. control, cisplatin-control, cisplatin and EO (150, 300 and 600 mg/kg; p.o. respectively in different groups) and EO only (600 mg/kg; p.o. only). EO was administered orally to the rats for a period of 10 days and on the 7th day, a single injection of cisplatin (8 mg/kg; i.p.) was administered to the cisplatin-control and EO treatment groups. The rats were sacrificed on the 10th day. Cisplatin-control rats had deranged renal function parameters and the kidney histology confirmed the presence of acute tubular necrosis. Furthermore, there were increased oxidative stress, apoptosis and inflammation along with higher expression of MAPK pathway proteins in the rat kidney from the cisplatin-control group. Contrary to this, EO (600 mg/kg) significantly normalized renal function, bolstered antioxidant status and ameliorated histological alterations. The inflammation and apoptosis were markedly lower in comparison to cisplatin-control rats. Furthermore, EO (600 mg/kg) inhibited MAPK phosphorylation which was instrumental in preserving renal function and morphology. In conclusion, the results of our study demonstrated that EO attenuated cisplatin-induced nephrotoxicity in rats through suppression of MAPK induced inflammation and apoptosis.